2020
DOI: 10.1111/1750-3841.15502
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the morphological property and chemical composition of soluble and insoluble dietary fiber with bound phenolic compounds from different algae

Abstract: The morphological, physicochemical, and biochemical properties of soluble and insoluble dietary fiber from seven types of algae were investigated. The soluble dietary fiber (SDF) contents (6.48 to 60.90% of the total fiber) in most of the investigated algae were significantly lower than the insoluble dietary fiber (IDF) contents (39.10 to 93.52% of the total fiber). It can be inferred from the infrared and UV‐Vis spectra that the SDF and IDF of algae may contain cellulose, hemicellulose, various monosaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Bound phenolics from marine brown seaweeds have gained seldom attention, although only a few studies have identified the composition of bound phenolics released from soluble dietary fiber and insoluble dietary fiber from algae by LC‐MS (Luo et al., 2020 ). This study investigated the method suitable for extracting bound phenolics from S. polycystum for the first time, indicated by the difference not only in TPC, TFC and antioxidant ability, but also in the profiles of bound phenolics between different hydrolysis methods.…”
Section: Resultsmentioning
confidence: 99%
“…Bound phenolics from marine brown seaweeds have gained seldom attention, although only a few studies have identified the composition of bound phenolics released from soluble dietary fiber and insoluble dietary fiber from algae by LC‐MS (Luo et al., 2020 ). This study investigated the method suitable for extracting bound phenolics from S. polycystum for the first time, indicated by the difference not only in TPC, TFC and antioxidant ability, but also in the profiles of bound phenolics between different hydrolysis methods.…”
Section: Resultsmentioning
confidence: 99%
“…The content of phenolic compounds presumably also accounts for the antibacterial properties observed in dispersed powdered algae biomass [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…The high absorbency ranged of 1,085 cm −1 was the characteristic absorption peak of polysaccharides. A strong stretching vibration at around 1,700 cm −1 (C=O) indicated the presence of carboxyl groups (Luo et al, 2020).…”
Section: The Structural Characterization Of L Japonica Dfmentioning
confidence: 99%